Synthesis and Antibacterial Activity of Some Fluorine Containing 2-Pyrazolines - Desai, M.D.; Desai, K.K. (Asian Journal of Chemistry, 2010)
Several new 1-carboxamido-3-[2´-hydroxy-4´-(p-trifluoromethyl phenoxy) phen-1´-yl]-5-substituted aryl-2-pyrazolines (II) have been prepared by reaction of 1-[2´-hydroxy-4´-(p-trifluoromethyl phenoxy)-phen-1´-yl]-3-substited aryl 2-propen-1-ones (I) with semicarbazide hydrochloride in ethanol. Few of these compounds are characterised by IR and NMR spectra. All these synthesized pyrazolines have been screened against a few microorganisms for antibacterial activity.